Rating the Acting Moment: Exploring Characteristics for Realistic Portrayals of Characters - Panero, Maria Eugenia; Winner, Ellen (Frontiers in Psychology, 2021)
Good actors appear to become their characters, making them come alive, as if they were real. Is this because they have succeeded in merging themselves with their character? Are there any positive or negative psychological effects of this experience? We examined the role of three characteristics that may make this kind of merging possible: dissociation, flow, and empathy. We also examined the relation of these characteristics to acting quality. Acting students (n = 44) and non-acting students (n = 43) completed a dissociation measure, and then performed a monologue that was recorded and rated on dimensions of acting. Participants were then reassessed on dissociation to determine whether it increased as a function of performance. They were also then assessed on flow and empathy. Actors did not differ from non-actors on dissociation, but did score significantly higher than non-actors on some flow and empathy subscales, indicating a positive psychological experience and outcome. While non-actors’ dissociation marginally increased post-performance, actors’ dissociation rose significantly, which could indicate a negative psychological experience. Surprisingly, acting ratings were unrelated to levels of dissociation, flow, or empathy. We conclude that, while these are tools used by actors to immerse themselves fully in their characters, they may not be necessary to create the illusion of an imaginary character come to life on stage.